The Interactive Effects of Type of Audit Firm, Managing Director Changes and Financial Distress on Auditor Independence in UK - Yu, Qingqing (2010)
Audit places an essential role in providing additional assurance on the credibility of company’s financial statements. It is important for policy makers to identify the factors which influence companies’ decisions to switch their auditor. This study is intended to examine the interactive effects of type of audit firm, managing director changes and financial distress together with audit qualification and other four control variables (auditee size; audit fees, growth rate of auditee and gearing) on auditor switching. Based on the data collected from 53 UK listed companies between 2007 and 2009, it finds that type of audit firm is perceived to be the first order important factor on propensity to switch, indicating that clients prefer reputable audit firms. Change in managing director is more important to explain auditor switching than financial condition. Other findings revealed that qualified audit opinion is not statistically associated with subsequent audit switching, implying the general enhancement in audit independent in UK as opinion shopping tend to be less frequent. However, it finds in addition that financial distressed companies are less likely to change auditor. This finding does not support the preceding analytical studies.